Developing Snakes and Ladders as a Civic Education Tool for Vocational High Schools - Jati, Dionisius Heckie Puspoko; Boriboon, Gumpanat (Universitas Negeri Semarang, 2024)
The Snakes and Ladders Game is a civic education learning media designed for vocational high school students to promote understanding and social cohesion among diverse populations. This innovative approach aims to enhance understanding through educational games that facilitate discussions about cultural, racial, ethnic, and religious diversity. This research aims to determine the effectiveness, feasibility and validity of the Snakes and Ladders learning program on diverse content for Class XI Vocational Schools in the context of Bhinneka Tunggal Ika. The ADDIE model is applied in this research approach. The population in the study were 214 students of grade XI at SMK Saraswati. While the sample in this study was one class with 30 students. The instruments used in this research were a questionnaire on the practicality of teacher and student responses, a material expert validation questionnaire, a media expert validation questionnaire, and an exam in the form of questions related to the material. Media expert validators got a score of 78.3%, material expert validators got a score of 82.8%, and potential user validators got a score of 75.5 in this snakes and ladders media development research. The average percentage score obtained by learning material experts was 78.3%, meeting the requirements very well. In this study, the new idea is to use snakes and ladders which are played by the students themselves. The development of this learning media can improve students' understanding in following PPKn learning. The learning media used is the snake and ladder media. Teachers are expected to use interesting learning media to increase students' learning motivation.